Genome-Wide Identification and Analysis of the Phosphoenolpyruvate Carboxylase Gene Family in Suaeda aralocaspica, an Annual Halophyte With Single-Cellular C4 Anatomy - Cao, Jing; Cheng, Gang; Wang, Lu; Maimaitijiang, Tayier; Lan, Haiyan (Frontiers in Plant Science, 2021)
Phosphoenolpyruvate carboxylase (PEPC) plays pivotal roles in carbon fixation of photosynthesis and a variety of metabolic and stress pathways. Suaeda aralocaspica belongs to a single-cellular C4 species carrying out the photosynthetic pathway within an unusually elongated chlorenchyma cell, which is expected to have PEPCs of different characteristics. To identify different isoforms of PEPC genes in S. aralocaspica, and comparatively analyze their expression and regulation patterns, as well as the biochemical and enzymatic properties, in the present study, we characterized a bacterial-type PEPC (SaPEPC-4) in addition to the two plant-type PEPCs (PTPCs, SaPEPC-1 and SaPEPC-2) by a genome-wide identification. The SaPEPC-4 presented a lower expression level in all test combinations with unknown function; two SaPTPCs showed distinct subcellular localizations and different spatio-temporal expression patterns, but both positively responded to abiotic stresses. The expression of SaPEPC-1 specifically in tissues with chlorenchyma cells was much more active with development progression and to various stresses compared to SaPEPC-2, particularly sensitive to light, implying the involvement of SaPEPC-1 in C4 photosynthesis pathway. In contrast, SaPEPC-2 was more like a non-photosynthetic PEPC. The expression trends of two SaPTPCs in response to light, development and abiotic stresses also matched with the changes of PEPC activity in vivo (native) or in vitro (recombinant), and the biochemical properties of two recombinant SaPTPCs were similar in response to various effectors, while the catalytic efficiency, substrate affinity and enzyme activity of SaPEPC-2 were higher than that of SaPEPC-1 in vitro. All the different behaviors presented between these two SaPTPCs might be involved in transcriptional (e.g., specific cis-elements), post-transcriptional (e.g., 5’-UTR secondary structure), or translational (e.g., PEPC phosphorylation/de-phosphorylation) regulatory events. These comparative studies on different isoforms of PEPC gene family in S. aralocaspica may help to decipher their exact role in C4 photosynthesis, plant growth/development and stress resistance.